Plantar Loading Forces While Walking in a Below-Knee Cast With an Attached Loadbearing Frame - Berwin,JT; Burton,TMW; Taylor,J; McGregor,AH; Roche,A (Foot & Ankle International, 2015)
Background: We measured loading forces across different points of the plantar foot surface to examine how different types of casts affect load distribution through the foot and ankle. The patella tendon-bearing (PTB) or Sarmiento cast is the current “gold-standard” casting method for offloading force through the foot and ankle. We aimed to determine if a rocker bottom frame attached to a below-knee cast (Beagle Böhler Walker) would be as effective or better at reducing load distribution during full weightbearing.Method: We applied TekScan FlexiForce A201 force sensors to the first and fifth metatarsal heads and the plantar surface of the calcaneus of 14 healthy volunteers. All volunteers had force measurements taken without a cast applied and then with a traditional Sarmiento cast, a standard below-knee cast, and a below-knee cast with the Böhler Walker frame fitted.Results: Compared with a standard below-knee cast, the Böhler Walker frame reduced the mean peak force through the head of the first metatarsal by 58.9% (P < .0001), 73.1% through the head of the fifth metatarsal (P < .0001), and 32.2% (P < .0001) through the calcaneus. The Sarmiento cast demonstrated a mean percentage reduction in peak force of 8.6% (P = .39) and 4.4% (P = .87) through the first and fifth metatarsal heads, respectively, but increased the mean peak force by 5.9% (P = .54) through the calcaneus.Conclusion: Using a Böhler Walker frame applied to a below-knee cast significantly reduced weight transfer through the foot compared with a Sarmiento cast or standard below-knee cast.Clinical Relevance: This reduction in force through the foot could mean early weightbearing would be safer in patients with a wide variety of foot and ankle pathologies such as ankle fractures or operative fixations. This may reduce the incidence of immobility-dependent morbidity.